2018
DOI: 10.22159/ajpcr.2018.v11i10.25577
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Bioactive Components in Enhalus Acoroides Seagrass Extract by Gas Chromatography–mass Spectrometry

Abstract: Objective: This study deals with the determination of possible phytocompounds present in the ethyl acetate extract of Enhalus acoroides using gas chromatography-mass spectroscopy (GC-MS) technique. Methods: Using GC-MS technique the phytocompounds present in the ethyl acetate extract of E. acoroides whole seagrass was investigated, and the mass spectra of the compounds found in the extract were matched with the National Institute of Standards and Technology library.Results: GC-MS analysis of E. acoroides extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…VOCs are complex secondary metabolites of plants. Amudha (2018) mentioned that tetracontane has antioxidant and cytoprotective activity.…”
Section: Resultsmentioning
confidence: 99%
“…VOCs are complex secondary metabolites of plants. Amudha (2018) mentioned that tetracontane has antioxidant and cytoprotective activity.…”
Section: Resultsmentioning
confidence: 99%
“…Siswadi and Saragih, [44] have reported that hexadecanoic acid, and ethyl ester have antioxidant, antimicrobial, and anti-inflammatory activity. Heptadecane, 9-hexyl-and 1,2-benzenedicarboxylic acid, and diisooctyl ester have antifungal activity [45][46][47]. Hexasiloxane, 1,1,3,3,5,5,7,7,9,9,11, 11-dodecamethyl have antimicrobial, antibacterial, antiseptic, hair conditioning agent, and emollient properties [48].…”
Section: Discussionmentioning
confidence: 99%
“…Alkanes function as protective wax in plants and reduce desiccation, abrasion, or resist pest attack (Maffei, 1994). The major compound, tetratetracontane, has the potential of an antioxidant (Amudha et al, 2018).…”
Section: Chemical Composition Of C Macrophylla Hexane Extract (Cmhe)mentioning
confidence: 99%